Att introducera språklig mångfald och migration som tema på mellanstadiet - Anna Lindholm; Lise Iversen Kulbrandstad; Birgitta Ljung Egeland (Dalarna university, 2023)
This article explores the didactic choices four Swedish teachers make, as they introduce three lesson plans about linguistic diversity and migration in upper elementary school. In addition, teachers' reflections on these choices and what new knowledge students develop, are examined. To analyze the choices teachers make, we use theory that sees teachers' professional practices as potentially powerful. The collected data consists of classroom observations and teacher interviews. The results show that the theme of linguistic diversity and migration engages both teachers and students. In addition, the teachers describe the theme as important, but confirm that they have not previously seen it addressed in teaching materials. Neither in the previous curriculum (Lgr11) nor in the current one (Lgr22) are issues of linguistic diversity included within the Swedish subject. Given the increasing number of students from diverse linguistic backgrounds in schools, we argue that knowledge about linguistic diversity is something that benefits all students as they grow up in a multilingual society. Promoting students' interest in different languages and cultures at an early age and encouraging positive attitudes are important tasks for teachers.